ANALISIS KINERJA KEUANGAN PERUSAHAAN PUPUK ORGANIK CV MULIA ORGANIK TURI SLEMAN - Sunardi, Sunardi (Jurnal Pengembangan Penyuluhan Pertanian, 2018)
ABSTRACTThe purpose of this study was to analyze the financial perknmance uf Organicfertilizer companies, CV Mulia Organik from a financial perspective span during 20_14- 2016. This research was a case study, the method of selection used purposive sampling. While respondents composite nine respondents employees and two respondents CV Mulia Organik customers. Methods of data collection obtained from secondary data with documentation. This research was conducted using Current Ratio (CR), Return On Asset (ROA) and Profit Margin On Sales (PMOS). The results obtained result that overall financial performance of CV Mulia Organik, its performance not good.Keywords: Performance, Finance, Organic Fertilizer.